Emotions and motivations of gambling: A comparison between scratch card, slot‐machines, and casino gamblers - Laura Ferro; Maria Grazia Monaci; Luca Scacchi (Brain and Behavior, 2024)
Abstract Introduction In the last 20 years, gambling has become more and more widespread in Italy. The aim of the present study is to compare the motivations for gambling and the emotions felt while gambling in three different subgroups: scratch card gamblers, slot‐machine gamblers, and casino gamblers. Methods Three versions of a questionnaire have been distributed in a casino, in scratch card vendors, and slot‐machines venues. All versions included sociodemographic variables, the two‐question Lie‐Bet instrument, a scale for motivations toward gambling, and a list of positive and negative emotions felt while gambling. Results Participants (N = 425, F 47.5%) are gamblers potentially pathological (N = 162, 38.1%) and not (N = 263, 61.9%). Different games seem connected to different motivations and emotions: the scratch gamblers show less Coping and Social Motivation and experience less Negative Emotion. However, the motivation and emotion most intensely experienced by the gamblers (Enhancement and the Positive Emotions) do not show differences between the different types of games. Conclusion The pathological gamblers have a more intense and internal connection with the game (have more Enhancement and Coping motives, Positive and Negative Emotion). In sum, our findings support the theoretical hypothesis that gambling can be a tool for regulating emotions.